Long-term effects of timber management on marten (Martes americana) habitat potential in an Ontario boreal forest - McCallum, Ian Ross (1993)
To evaluate the hypothesis that current forest management practices in the boreal forest are decreasing the quantity and quality of long-term marten habitat, and alternative, more suitable strategies exist, a Geographic Information System (GlS)-based simulation study was initiated to determine the habitat suitability for marten of a boreal forest under various timber management strategies. Two simulation models were used in this study. The first was the Harvest Schedule Generator (HSG), a wood-supply model created at the Petawawa National Forestry Institute (Forestry Canada). The second was a marten Habitat Suitability Index (HSI) model developed for this study. Each of the timber harvest strategies decreased the amount of long-term marten habitat. However, slight decreases in the level of spruce harvest provide significant future increases in suitable habitat. In the short term, delayed harvest of mature black spruce stands provides an improvement in marten habitat suitability. The procedures developed in this study provide valuable quantitative information which can be used to aid in forest management decision making.